Food independence as indicator of the food safety estimation of Ukraine - Сухий, Петро; Тюфтій, Алла; Ячнюк, Марина (Human Geography Journal, 2017)
In the current environment, the food security should be considered as a first-order condition not only for preservation of the state system, but also for population’s physical survival. In this context, it seems actual to analyze such important component as food sovereignty which is understood as the level of annual production of vital foodstuffs manufactured inside the country with the given level of development of productive forces and in accordance with the given set of direct materials and foodstuffs recommended by the public health bodies as rational (minimal) rate of consumption. Thorough analysis of theoretical-methodological studies; statistical data available with the FAOSTAT; and author’s practice allow for development of the scale of the levels of food sovereignty (LFS). The level of FS is considered full if the value of the share of own production of major foodstuffs no less than 80%; the share amounts between 60% and 80% shall be considered as above average; and the level of manufactured alimentary raw materials and foodstuffs amounting to 40-60% shall be considered as average satisfaction. The LFS is considered partial if ranges within 20-40%, dangerous – 10-20%, and critical – less than 10%. It is also worth mentioning that, among ten basic foods included into consumer basket of average citizen of Ukraine, bread and cereal products, milk, meat and meat processing products, hen’s eggs, potatoes, vegetables and gourds, sugar and plant oil comprise the most common and important part of such citizen’s ration. In the process of study, we have calculated the potential of consumer demand in population of Ukraine in 2014 proceeding from actual consumption and following the minimal and rational consumption rates. With minimal consumption, the potential amounted to UAH6632,7 million, while the figure of this potential when people would consume at recommended rates was colossal amounting to annual almost UAH 147 milliard.